Secure Data Management - Jonker, Willem (Springer - Verlag, 2011)
This book constitutes the refereed proceedings of the Second VLDB 2005 International Workshop on Secure Data Management, SDM 2005, held in Trondheim, Norway in August/September 2005 in conjunction with VLDB 2005.